Assessing the Role of the Work Environment in Enhancing Employee Job Satisfaction: Insights from a Local Government Organization in Indonesia - Nur Syifa Aulia Hasna; Ikhwani Ratna; Najima Najima (International Journal of Information System and Innovation Management (IJISIM), 2026)
This study is motivated by work environment problems in the Regional Secretariat General Administration Assistant Section of Indragiri Hilir Regency, including limited facilities, suboptimal workspace conditions, and relationship dynamics affecting employee job satisfaction. The study aims to analyze the effect of the work environment on employee job satisfaction. A quantitative survey method was applied. Data were collected through questionnaires from 65 respondents, supported by interviews, observation, and documentation. Analysis techniques included validity and reliability tests, simple linear regression, coefficient of determination, and t-test. Results indicate that the work environment has a positive and significant effect on employee job satisfaction. Comfortable workplaces, harmonious relationships, effective communication, and adequate facilities improve job satisfaction. Although some facility limitations remain, the overall work environment is categorized as good and supports employee performance. The conclusion shows that a better work environment increases employee job satisfaction in the institution. These findings highlight the importance of improving workplace conditions to enhance organizational effectiveness and employee satisfaction levels.